2004
DOI: 10.1074/jbc.m409964200
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of the 185–189-Loop in the Factor Xa Interaction with Na+ and Factor Va in the Prothrombinase Complex

Abstract: The S1 site (Asp 189 ) of factor Xa (fXa) is located on a loop (residues 185-189) that contains three solvent-exposed charged residues (Asp 185 , Lys 186 , and Glu 188 ) below the active-site pocket of the protease. To investigate the role of these residues in the catalytic function of fXa, we expressed three mutants of the protease in which the charges of these residues were neutralized by their substitutions with Ala (D185A, K186A, and E188A). Kinetic studies revealed that E188A has a normal catalytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
66
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 34 publications
8
66
0
Order By: Relevance
“…1). Furthermore there is some evidence that both the FVa-and Na ϩ -binding sites of FXa are energetically linked (20,23). Altogether these observations suggest that there is an allosteric linkage between the Na ϩ -binding site and FVa-binding h163-170.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…1). Furthermore there is some evidence that both the FVa-and Na ϩ -binding sites of FXa are energetically linked (20,23). Altogether these observations suggest that there is an allosteric linkage between the Na ϩ -binding site and FVa-binding h163-170.…”
supporting
confidence: 55%
“…It has been demonstrated previously that the amidolytic activity of FXa is not dependent on the ionic strength of the reaction buffer in the range of NaCl used (19,23,30). Thus, no compensating chloride salt was added to the reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Curiously, the original observation on thrombin was at odds with the accepted view at the time that salts, and Na ϩ in particular, actually acted as inhibitors of thrombin hydrolysis of synthetic substrates (17,18). In fact, the inhibitory effect of Na ϩ was rationalized as a direct perturbation of the catalytic His 57 that would reduce effectiveness of the charge relay system (18). Wells and Di Cera demonstrated that the Na ϩ activation of thrombin is specific and allosteric and involves the transition of the enzyme between two active forms (19) leading to an increase in k cat and a decrease in K m .…”
mentioning
confidence: 73%
“…More recent studies have shown that parts of this helical region appear linked to the S1-and Na ϩ binding sites (56), lending further support to the idea that changes in the activation domain will likely impact FVa binding. Furthermore, mutagenesis studies have shown that the Na ϩ binding site and the 185-189 loop are important for FVa binding (19,23,24,57 . Aliquots of the reaction mixture were quenched during the initial rate of the reaction (0, 0.5, 1, 1.5, and 2.0 min), and thrombin generation was determined by using the chromogenic substrate S-2238.…”
Section: Discussionmentioning
confidence: 99%